Physiologically Based Biopharmaceutics Modeling Coupled with Biopredictive Dissolution in Development of Bioequivalent Formulation for Mesalamine Enteric Coated Tablet: A Tough Nut to Crack - Kollipara, Sivacharan; Prabhat, Pankaj Kumar; Saha, Paramita; Gupta, Saurabh; Naidu, Venkat Ramana; Ahmed, Tausif (AAPS PharmSciTech, 2024)
Mesalamine is a locally acting anti-inflammatory drug used to treat mild to moderate ulcerative colitis. Because of complex formulation principle and high in vivo variability, development of bioequivalent formulation for mesalamine is challenging. Further, fed state possess significant challenges for bioequivalence (BE) due to interplay of multiple factors. In the work, we have developed a novel biopredictive media for mesalamine enteric coated tablets and integrated into physiologically based biopharmaceutics model (PBBM) to predict in vivo fed behavior. USP III based gradient media was developed to mimic in vivo fed condition. The developed PBBM was initially validated with literature data and subsequently re-optimized with pilot BE study data. Further, virtual bioequivalence (VBE) was performed to evaluate model predictability for pilot BE data. Later, the model was applied for prospective BE predictions with increased subjects and parametric sensitivity analysis was performed to identify physiological factors that can impact in vivo performance. Further, the model was used to predict luminal and enterocyte concentrations in colon to demonstrate equivalent efficacy. Additionally, a novel dissolution/permeation tool (Dissoflux) was employed to compare permeability behavior of formulations. Overall, this work enabled BE prediction for complex mesalamine enteric coated tablets and helped to understand parameters that can impact in vivo performance. Graphical Abstract